Sistem Informasi Geografis Gardu Listrik PT. PLN (Persero) APJ MAJALAYA - Aditya Galih Sulaksono (Jurnal Teknologi dan Manajemen Informatika, 2016)
Geographic Information System is a system information that aims to present information in depreciation and includes objects - objects the ADA on the surface of the earth and DI hearts. Different advantages offered by depreciation and information system, including the presentation of Adjusted with the user requirements system, with statistical analysis using different visualization The Typical And Able advantages offered through the analysis of depreciation and drawings through the map / floor plan. Design of information systems depreciation and combine raw data company between the map data can be simplify decision hearts put substation electrical installation nearby. DOI: https://doi.org/10.26905/jtmi.v2i1.604